Small‐scale indirect plant responses to insect herbivory could have major impacts on canopy photosynthesis and isoprene emission. Issue 3 (26th July 2018) - Visakorpi, Kristiina; Gripenberg, Sofia; Malhi, Yadvinder; Bolas, Conor; Oliveras, Imma; Harris, Neil; Rifai, Sami; Riutta, Terhi
Summary: Insect herbivores cause substantial changes in the leaves they attack, but their effects on the ecophysiology of neighbouring, nondamaged leaves have never been quantified in natural canopies. We studied how winter moth ( Operophtera brumata ), a common herbivore in temperate forests, affects the photosynthetic and isoprene emission rates of its host plant, the pedunculate oak ( Quercus robur ). Through a manipulative experiment, we measured leaves on shoots damaged by caterpillars or mechanically by cutting, or left completely intact. To quantify the effects at the canopy scale, we surveyed the extent and patterns of leaf area loss in the canopy. Herbivory reduced photosynthesis both in damaged leaves and in their intact neighbours. Isoprene emission rates significantly increased after mechanical leaf damage. When scaled up to canopy‐level, herbivory reduced photosynthesis by 48 ± 10%. The indirect effects of herbivory on photosynthesis in undamaged leaves (40%) were much more important than the direct effects of leaf area loss (6%). If widespread across other plant–herbivore systems, these findings suggest that insect herbivory has major and previously underappreciated influences in modifying ecosystem carbon cycling, with potential effects on atmospheric chemistry. Abstract : See also the Editorial byKessler, 220 : 655–658 .